Let "z-x=u", then "z=x+u" and "dz=dx+du".
Rewrite the equation replacing "z" by "x+u":
"(1+xy+yu)dx+xudy-(1+xy)dx-(1+xy)du=0"
After simplification we obtain "yudx+xudy-(1+xy)du=0"
Note that "xdy+ydx=d(xy+1)", so we have "ud(1+xy)-(1+xy)du=0".
After dividing it by "(1+xy)^2" we obtain "d\\left(\\frac{u}{1+xy}\\right)=-\\frac{ud(1+xy)-(1+xy)du}{(1+xy)^2}=0", so "\\frac{u}{1+xy}=C"
Since "u=z-x", we have "\\frac{z-x}{1+xy}=C". After expressing "z" we obtain "z=x+C(1+xy)"
Answer: "z=x+C(1+xy)"
Comments
Leave a comment